Mechanical Stimulation on Mesenchymal Stem Cells and Surrounding Microenvironments in Bone Regeneration: Regulations and Applications - Sun, Yuyang; Wan, Ben; Wang, Renxian; Zhang, Bowen; Luo, Peng; Wang, Diaodiao; Nie, Jing-Jun; Chen, Dafu; Wu, Xinbao (Frontiers in Cell and Developmental Biology, 2022)
Treatment of bone defects remains a challenge in the clinic. Artificial bone grafts are the most promising alternative to autologous bone grafting. However, one of the limiting factors of artificial bone grafts is the limited means of regulating stem cell differentiation during bone regeneration. As a weight-bearing organ, bone is in a continuous mechanical environment. External mechanical force, a type of biophysical stimulation, plays an essential role in bone regeneration. It is generally accepted that osteocytes are mechanosensitive cells in bone. However, recent studies have shown that mesenchymal stem cells (MSCs) can also respond to mechanical signals. This article reviews the mechanotransduction mechanisms of MSCs, the regulation of mechanical stimulation on microenvironments surrounding MSCs by modulating the immune response, angiogenesis and osteogenesis, and the application of mechanical stimulation of MSCs in bone regeneration. The review provides a deep and extensive understanding of mechanical stimulation mechanisms, and prospects feasible designs of biomaterials for bone regeneration and the potential clinical applications of mechanical stimulation.